Implementing open source cloud platform as an enterprise solution and develop a tool to manage the entire ecosystem - Hossain, Md. Imran (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.